Significance of cyclooxygenase-2 in oncogenesis - Szweda Marta (Journal of Veterinary Research, 2019)
The cyclooxygenase-2 (COX-2) enzyme catalyses the first stage of biosynthesis of prostanoids, proteins that are implicated in various physiological and pathological processes in humans and animals. The expression of COX-2 increases significantly during pathological processes accompanied by inflammation, pain and fever. Overexpression of COX-2 was determined in tumour tissues, which suggests that this enzyme participates in oncogenesis. In this paper the topics discussed are mechanisms regulating COX-2 expression, COX isoforms, their role in the body and the oncogenic mechanisms triggered by the overexpression of COX-2, including inhibition of apoptosis, intensification of neoangiogenesis, increased metastatic capacity, and weakening of the immune system. The significance of and the mechanisms by which COX-2 participates in oncogenesis have been studied intensively in recent years. The results are highly promising, and they expand our understanding of the complex processes and changes at the molecular, cellular and tissue level that promote oncogenesis and cancer progression. Notwithstanding the knowledge already gleaned, many processes and mechanisms have not yet been elucidated in human medicine and, in particular, in veterinary medicine. Further research is required to develop effective tumour diagnostic methods and treatment procedures for humans and animals.